KONSEP KEUNGGULAN PENDIDIKAN MADRASAH INSAN CENDEKIA - Munawaroh; Syamsul Aripin (Pascasarjana Universitas Al-Qolam Malang, 2025)
Madrasah Aliyah Negeri Insan Cendekia (MAN IC) is a model of an Islamic boarding school at the secondary education level, which combines the uniqueness of Islamic religious education with the enrichment of science and technology. MAN IC has continued to develop in quality and quantity since it was handed over to the Department of Religion. In terms of quality, MAN IC produces very proud outputs, with many achievements both nationally and internationally. MAN IC was developed by the Ministry of Religion with the aim of expanding access to education for high-achieving students from both high and low economic backgrounds, with the government fully covering the costs. This research aims to analyze the concept of MAN IC education through a literature review of various relevant literature sources. This research uses Library Research or literature research as its main approach. This method involves searching and analyzing relevant literature related to the research topic. Data for this research was obtained from scientific literature sources such as journals and books related to the Concept of Madrasah Aliyah Negeri Insan Cendikia. The conclusion of this research indicates that the MAN IC education concept successfully integrates Islamic religious education with science and technology through an integrated curriculum, innovative learning methods, and a comprehensive coaching system. This concept emphasizes the holistic development of student potential, encompassing intellectual, spiritual, and social aspects, and produces high-achieving and outstandingly characterized graduates.